Metodologias ativas de aprendizagem para a Educação a Distância: uma análise didática para dinamizar sua aplicabilidade - Rosa Junior, Luiz Carlos (2015)
This research presents a study on how active methodologies that can streamline distance education through the use of technological resources. The intention is to identify the real need for adjustments along the existing technological resources in the market for contemplating the directives contained among the methods researched and analyzed in order to make it feasible for use in a distance learning course. In this sense, approaches will be carried out during the work in order to score relevant requirements for the use of a virtual learning environment (Moodle), along with its features and integrated tools (BigBlueButton) so that they can serve as a tool for learning together with the use of active methodology (Peer Instruction). A simulation class in this way was applied with a group of students of a classroom course. The expected results were satisfactory with regard to the implementation of the proposal. Analyzing this work can be justified by a need to review and display of teaching content from a distance, effective and motivating way supported by a technological resource. The use of this technological resource increased by an active methodology can improve the qualitative potential for this type of education